Performance Prediction Based on Effects of Wrapping Angle of a Side Channel Pump - Ji Pei; Fan Zhang; Desmond Appiah; Bo Hu; Shouqi Yuan; Ke Chen; Stephen Ntiri Asomani (Energies, 2019)
This paper seeks to predict the performance of the side channel pump by considering the influences of different wrapping angles. Firstly, three pump cases 1, 2 and 3 are modeled with wrapping angles 15°, 30° and 45°, respectively. Secondly, different physical parameters comprising exchanged mass flow, pressure and velocity distributions are plotted at the best efficiency point (QBEP) to analyze the internal flow characteristics. Since the flow exchange times depend on the size of the wrapping angle, the size of the wrapping angle has significant effects on the pump head performance. Case 1 with the smallest wrapping angle recorded the largest head improvement at all operating conditions compared to case 2 and case 3. Case 1 at QBEP attained a head coefficient increase of about 9.8% and 38.6% compared to that of case 2 and case 3, respectively. However, the size of the wrapping angle had a slight effect on the pump efficiency; thus, case 1 still predicted a marginal increase in efficiency compared to case 2 and case 3 at all operating conditions. Lastly, the numerical simulations were validated with experimental data after manufacturing pump case 2.